2012
DOI: 10.1108/09684881211240330
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Malaysian higher education quality culture and workforce performance

Abstract: Purpose -The purpose of this study is to examine the relationship between the quality culture and workforce performance in the Malaysian higher education sector. The study also aims to test and validate the psychometric properties of the quality culture and workforce performance instruments used in the study. Design/methodology/approach -A total of 267 academic staff from the International Islamic University Malaysia completed the survey questionnaires. A principal component analysis (PCA) technique was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 16 publications
5
27
0
Order By: Relevance
“…Process quality improvement is achieved through a workforce that follows the HEI's strategies, thus maintaining a high-performance workplace focused on the students, which justifies the direct relationship with both operations and results. These findings are consistent with those of [68], who concluded that when the university establishes a quality control-oriented workplace, it is more likely that academic staff will be satisfied and therefore work constructively for the cause of organizational success.…”
Section: Discussionsupporting
confidence: 90%
“…Process quality improvement is achieved through a workforce that follows the HEI's strategies, thus maintaining a high-performance workplace focused on the students, which justifies the direct relationship with both operations and results. These findings are consistent with those of [68], who concluded that when the university establishes a quality control-oriented workplace, it is more likely that academic staff will be satisfied and therefore work constructively for the cause of organizational success.…”
Section: Discussionsupporting
confidence: 90%
“…T. Lee, 2014) with the academic staff population of 33,000 in public universities and 2,500 in private institutions (Wan et al, 2015), some research studies related to HE issues have been conducted. A few of these studies include the investigation of the relationship between the quality culture and workforce leadership performance in Malaysian HE (Ali & Musah, 2012); the issue of knowledge management, knowledge sharing, and research collaboration in Malaysian public universities (Tan & Md. Noor, 2013); strategic planning in Malaysian HEIs; university autonomy and political uncertainties (Sirat, 2010); global trends; national policies and institutional responses toward restructuring of Malaysian HE (M. N. N. Lee, 2004); internationalization challenges in Malaysia (Karim & Maarof, 2012); leadership crisis in Malaysian public universities (Sirat, Ahmad, & Azman, 2012); and the main issues of Malaysian public and private HEIs (M. N. N. Lee, 2015).…”
Section: Research-article20182018mentioning
confidence: 99%
“…With respect to Asia Pacific region and particularly Malaysia, a limited number of studies have been carried out to address the key issues and challenges in Malaysian HE. Among these issues, the income and employment multipliers in Malaysian HE (Yen et al 2015), Malaysian academic culture (Wan et al 2015), Internationalization of Malaysian HE (Abd Aziz and Abdullah 2014), and the relationship between the quality culture and workforce performance in Malaysian HE (Ali and Musah 2012) may be stated. In addition, the privatization of HE, corporatization of public universities, the challenges that universities encounter in terms of quality assurance, diversifying sources of funding, and internationalization of HE have been scrutinized (Lee 2015).…”
Section: Introductionmentioning
confidence: 99%